Pengaruh Tri-n-Oktil Posfin Oksida dan Tingkat Ekstraksi pada Pemurnian Konsentrat Thorium - Purwanti, M.V.; Moch. Setyadji (BRIN Publishing, 2015)
The extraction of thorium oxalate concentrate as processing product of monazite using Tri Octyl Posfine Oxide (TOPO) has been done. The most impurities contained in thorium oxalate concentrate are Ce (cerium) and La (lanthanum). The purpose of this study is to purify Th by separating Ce and La using extraction process. The extraction is done by bacth and multistage. The solution of feed or water phase is 10 grams of Th oxalate concentrate dissolved in 10.08 M HNO3 so that the volume becomes 100 mL and the organic phase is TOPO in kerosene. Stripping in each stage conducted three times, first stripping use water, second stripping use 5 % oxalic acid and the third stripping use water. Extraction time at every stage is 15 minutes and stripping time at every stage is 5 minutes with ratio of aqueous phase to organic phase = 1 : 1 . The parameters were studied % TOPO - kerosene and number of extraction stage. The optimum usage of TOPO in kerosene is 5 %. On extraction I obtained Ce concentrate and on extraction II and III obtained Th concentrates. The extraction II efficiency of Th is 39.76 % and extraction III efficiency of Th is 26.33 % . Coefficient of distribution (Kd) of Th in stage II is 0.7587 and Kd of Th in stage III is 1.0096. Total extraction efficiency of Th is 80.08 %, total extraction efficiency of Ce is 56.12 %, and total extraction efficiency of La is 1.54 %. The separation factor of Th – Ce in extraction I is 1.00 and separation factor of Th – La in extraction I is 92.0, separation factor of Th – Ce in extraction II is 250.24, and separation factor of Th – La in extraction II is ∞. Separation factor of Th – Ce in extraction III is 124.22 and separation factor of Th – La in extraction III is ∞. Total separation factor of Th – Ce is 1.4270 and total separation factor of Th – La is 4.0459. The content of Th oxalate in stripping product from the extraction II is 97.06 % and in stripping product from the extraction III is 98.00%.